Environmental enrichment and its effects on exhibit stereotypic behaviors in jaguars (Panthera onca) from the Yaguar Xoo Zoological Park, Oaxaca - Castillo-Guevara, Citlalli; Unda-Harp, Karime; Lara, Carlos; Serio-Silva, Juan Carlos (Instituto de Ecología, A.C., 2012)
The development of environmental enrichment programs to captive animals, promotes the animal welfare by increasing their physical activity as well as diminishing the stress, and preventing or reducing abnormal or stereotypic behaviors. In the Yaguar Xoo Zoological Park we designed and applied an environmental enrichment program to four captive jaguars (Panthera onca). Were two males (four and ten years old) and two females (four and ten years respectively). Enrichment items (teething and bag with stones) were applied, food (chicken, beef, fish, food shopping Whiskas®) and sensory (recordings of vocalizations of jaguar Panthera onca, puma Puma concolor and howler monkey Alouatta palliata, and as bags with different essences of mint, orange, anise, lynx Lynx rufus and ocelot Felis pardis urine). Our goal was to evaluate the program’s efficiency on the reduction or elimination of stereotypic behaviors (swinging, pacing, and vocalization). The exhibit behaviors were evaluated through three different phases: (1) the pre-enrichment phase (26 days), (2) the environmental enrichment application phase (34 days), and (3) the post-enrichment phase (22 days). As a result of the application program found a significant decrease in the performance of stereotypies and an increase in behavior normal individuals studied. For these four jaguars, the number of displayed normal behavior (whether they were individual or social) was significantly different among the three stage of the study (F2,306 = 4.215, p = 0.0156). In the post-enrichment frequency of normal behavior was similar to the pre-enrichment (p = 0.4680). The swinging (9.57%) decreased dramatically once applied environmental enrichement (0.96%) and, this trend continued even though the enrichment was removed (3.88%) (X2 = 102.9, p < 0.001). The pacing (1.96%) also fell dramatically once applied environmental enrichment (0.36%) and, once the enrichment was removed, the percentage increased to levels similar to the previous stage (1.26%) (X2 = 12.6, p < 0.001). The vocalization (3.06%) decreased dramatically once applied environmentalenrichment (0.48%), however was similar in the stages before and after the enrichment (3.49%)(X2 = 21.14, p < 0.001). In conclusion, the application of the environmental enrichment enhance captivejaguars’ well-being by stimulating active behaviors and reducing stereotypical behaviors.